Hawthorn fruit acid consumption attenuates hyperlipidemia-associated oxidative damage in rats - Feng, Yicheng; Gao, Shan; Zhu, Ting; Sun, Guibo; Zhang, Peisen; Huang, Yichun; Qu, Shuang; Du, Xiaomeng; Mou, Dehua (Frontiers in Nutrition, 2022)
Context: Hyperlipidemia (HLP) is a highly prevalent risk factor for atherosclerosis and stroke. The currently available medications used to treat Hyperlipidemia cannot improve its oxidative stress damage. Consumption of hawthorn can regulate blood sugar and blood lipids, and its rich fruit acid is a natural antioxidant that can improve oxidative stress damage. Objective: The present research aimed to investigate the protective effect of hawthorn fruit acid (HFA) on HLP and to determine its potential molecular mechanism. Materials and Methods: Sprague-Dawley rats were fed a high-fat diet (HFD) to induce HLP and treated orally with hawthorn fruit acids (HFA). Serum and liver levels of total cholesterol (TC), triglycerides (TG), high-density lipoprotein cholesterol (HDL-C), superoxide dismutase (SOD), hydrogen peroxide (CAT), and malondialdehyde (MDA) were measured. HepG2 cells were treated with 0.1 mM oleic acid and HFA (0.125, 0.25 mg/ml), and intracellular TC, TG, HDL-C, SOD, CAT and MDA were measured. changes in LDLR, HMGCR, Nrf2, HO-1, NQO1 protein and gene expression were analyzed by Western blot and qPCR. Results: This study found that HFA treatment effectively reduced triglyceride, cholesterol, and glucose levels and attenuated hepatic steatosis in rats. Additionally, oxidative stress damage in rats was effectively reduced by treatment with HFA. Western blot and qPCR analysis indicated that HFA treatment inhibited fat accumulation in HepG2 cells by upregulating LDLR and downregulating HMGCR gene expression, and inhibited oxidative damage to HepG2 by OA through activation of the Nrf2 / HO-1 signaling pathway. Conclusion: HFA administration can provide health benefits by counteracting the effects of hyperlipidemia caused by an HFD in the body, and the underlying mechanism of this event is closely related to the activation of the Nrf2/HO-1 signaling pathway.